2014
DOI: 10.1002/ijc.28906
|View full text |Cite
|
Sign up to set email alerts
|

Reduced promoter methylation and increased expression of CSPG4 negatively influences survival of HNSCC patients

Abstract: Proteoglycans are often overexpressed in tumors and can be found on several normal and neoplastic stem cells. In this study, we analyzed in-depth the role of CSPG4 in head and neck squamous cell carcinomas (HNSCC). Analysis of CSPG4 in a homogeneous study sample of HPV-negative stage IVa HNSCCs revealed overexpression of protein and mRNA levels in a subgroup of HNSCC tumors and a significant association of high CSPG4 protein levels with poor survival. This could be validated in three publicly available microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 33 publications
(68 reference statements)
3
36
3
Order By: Relevance
“…CSPG4 is an established marker for GBM, and previous studies have demonstrated that increased expression of CSPG4 in tumour cells and biopsies was associated with reduced patient survival, increased pathological severity, and MDR but was not associated with age or hypermethylation of the MGMT promoter (Stegmuller, Schneider, Hellwig, Garwood, & Trotter, ; Warta et al, ). These data indicated that activated CSPG4 signalling promoted the aggressive disease course and multidrug chemoresistance (Price et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…CSPG4 is an established marker for GBM, and previous studies have demonstrated that increased expression of CSPG4 in tumour cells and biopsies was associated with reduced patient survival, increased pathological severity, and MDR but was not associated with age or hypermethylation of the MGMT promoter (Stegmuller, Schneider, Hellwig, Garwood, & Trotter, ; Warta et al, ). These data indicated that activated CSPG4 signalling promoted the aggressive disease course and multidrug chemoresistance (Price et al, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors for HNSCC include epigenetic regulation of gene expression, which may lead to the induction and progression of HNSCC (Bragado et al, 2012;Hakami et al, 2014). Increasing evidence suggests that promoter methylation of tumor-related genes can aggravate the disease in HNSCC (Laytragoon-Lewin et al, 2013;Rettori et al, 2013;Warta et al, 2014;Shi et al, 2015). However, few studies have reported on the prognostic value of promoter methylation in HPV-induced HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules have been shown to be attractive potential biomarkers of cancer prognosis. For example, CSPG4/NG2 has been proposed as a prognostic marker for breast cancers [13], head and neck squamous cell carcinomas (HNSCC) [14] and gliomas [15,16]. The expression of nestin has been described in tumor and peritumor areas of GB, independently of the presence of neoplastic cells [17,18].…”
Section: Discussionmentioning
confidence: 99%